High‐throughput identification of factors promoting neuronal differentiation of human neural progenitor cells in microscale 3D cell culture. Issue 1 (27th October 2018) - Nierode, Gregory J.; Gopal, Sneha; Kwon, Paul; Clark, Douglas S.; Schaffer, David V.; Dordick, Jonathan S.
Abstract: Identification of conditions for guided and specific differentiation of human stem cell and progenitor cells is important for continued development and engineering of in vitro cell culture systems for use in regenerative medicine, drug discovery, and human toxicology. Three‐dimensional (3D) and organotypic cell culture models have been used increasingly for in vitro cell culture because they may better model endogenous tissue environments. However, detailed studies of stem cell differentiation within 3D cultures remain limited, particularly with respect to high‐throughput screening. Herein, we demonstrate the use of a microarray chip‐based platform to screen, in high‐throughput, individual and paired effects of 12 soluble factors on the neuronal differentiation of a human neural progenitor cell line (ReNcell VM) encapsulated in microscale 3D Matrigel cultures. Dose–response analysis of selected combinations from the initial combinatorial screen revealed that the combined treatment of all‐ trans retinoic acid (RA) with the glycogen synthase kinase 3 inhibitor CHIR‐99021 (CHIR) enhances neurogenesis while simultaneously decreases astrocyte differentiation, whereas the combined treatment of brain‐derived neurotrophic factor and the small azide neuropathiazol enhances the differentiation into neurons and astrocytes. Subtype specification analysis of RA‐ and CHIR‐differentiated cultures revealed that enhanced neurogenesis was not biased toward a specific neuronal subtype. Together, these results demonstrate a high‐throughput screening platform for rapid evaluation of differentiation conditions in a 3D environment, which will aid the development and application of 3D stem cell culture models. Abstract : We report the use of a chip‐based system for combinatorial high‐throughput differentiation screening of microscale three‐dimensional (3D) human neural progenitor cells (hNPCs).